Perancangan Sistem Informasi Inventory Produksi Pakaian Berbasis Web Dengan Metode Agile (Studi Kasus: Lie Konveksi) - Melinda; Anwar, Chairul (Journal of Information Systems and Business Technology, 2026)
In this study, various problems that occur in the convection lie are, The current obstacles are that recording is still done manually using note paper/books. Then for outgoing stock there is no accurate report on every e-commerce purchase or outside e-commerce. In addition, the current stock is uncertain in number so it is often recalculated to ensure the amount of stock available. Then there is no stocktaking for stock monitoring, there is no data for returned or refunded items, and there is no report for outgoing stock reports. Items that are in demand are often out of stock because there is no stock monitoring. The purpose of the study is to improve the efficiency of the stock recording process by designing a system that can reduce discrepancies, in addition to minimizing errors in recording stock data that often occurs due to human error factors, then to consider production on products that are in high demand and those that are less in demand. The method used is Agile Development as a reference for creating a system in this study, with the addition of several tools such as MySql as database storage and so on, here the author also uses UML (Unified Modeling Language) as documentation in creating this application and ERD (Entity Relationship Diagram) as a structure. The expected result is that this application can function properly as it should in the convection lie, with this inventory application it can facilitate employees in managing product stock, help in terms of work time efficiency, reduce human error, and support the right decision making in product management.